The effects of strontium on bone mineral: A review on current knowledge and microanalytical approaches. (January 2016) - Querido, William; Rossi, Andre L.; Farina, Marcos
Highlights: Strontium is incorporated into bone mineral during treatment with strontium ranelate. The incorporation of strontium into the nanocrystals may change their properties. The structure and composition of the mineral need to be evaluated at the nanoscale. Advanced microscopy and microanalytical methods show great potential for this analysis. Abstract: The interest in effects of strontium (Sr) on bone has greatly increased in the last decade due to the development of the promising drug strontium ranelate. This drug is used for treating osteoporosis, a major bone disease affecting hundreds of millions of people worldwide, especially postmenopausal women. The novelty of strontium ranelate compared to other treatments for osteoporosis is its unique effect on bone: it simultaneously promotes bone formation by osteoblasts and inhibits bone resorption by osteoclasts. Besides affecting bone cells, treatment with strontium ranelate also has a direct effect on the mineralized bone matrix. Due to the chemical similarities between Sr and Ca, a topic that has long been of particular interest is the incorporation of Sr into bones replacing Ca from the mineral phase, which is composed by carbonated hydroxyapatite nanocrystals. Several groups have analyzed the mineral produced during treatment; however, most analysis were done with relatively large samples containing numerous nanocrystals, resulting thus on data that represents an average of many crystalline domains. The nanoscale analysis of the bone apatite crystals containing Sr has only been described in a few studies. In this study, we review the current knowledge on the effects of Sr on bone mineral and discuss the methodological approaches that have been used in the field. In particular, we focus on the great potential that advanced microscopy and microanalytical techniques may have on the detailed analysis of the nanostructure and composition of bone apatite nanocrystals produced during treatment with strontium ranelate.